Transient cognitive impairment in the acute phase of stroke – prevalence, risk factors and influence on long-term prognosis in population of patients with stroke (research study – part of the PROPOLIS study) - Jakub Droś; Katarzyna Kowalska; Paulina Pasińska; Aleksandra Klimkowicz-Mrowiec (BMC Neurology, 2023)
Abstract Background Cognitive impairment is a common complication of the acute phase of stroke, which can be transient and resolve while still in the hospital. This study evaluated the prevalence and risk factors for transient cognitive impairment and their impact on long-term prognosis in a population of acute-phase stroke patients. Methods Consecutive patients admitted to a stroke unit with acute stroke or transient ischemic attack were screened twice for cognitive impairment using the parallel version of Montreal Cognitive Assessment: the first time between the first and third day and the second time between the fourth and seventh day of hospitalization. If the second test score increased by two or more points, transient cognitive impairment was diagnosed. Patients were scheduled for follow-up visits three and 12 months after stroke. Outcome assessment included place of discharge, current functional status, dementia, or death. Results Four hundred forty-seven patients were included in the study, 234 (52.35%) were diagnosed with transient cognitive impairment. Delirium was the only independent risk factor for transient cognitive impairment (OR 2.417, 95%CI 1.096–5.333, p = 0.029). In the analysis of effects on three- and twelve-month prognosis, patients with transient cognitive impairment had a lower risk of hospital or institution stay 3 months after stroke compared with patients with permanent cognitive impairment (OR 0.396, 95%CI 0.217–0.723, p = 0.003). There was no significant effect on mortality, disability or risk of dementia. Conclusions Transient cognitive impairment, which often occurs in the acute phase of stroke, does not increase the risk of long-term complications.